ผลของเคซีนฟอสโฟเปปไทด์ - อะมอร์ฟัสแคลเซียมฟอสเฟตต่อความแข็งของเคลือบฟันที่ถูกสึกกร่อนโดยเครื่องดื่มโคลา - หทัยชนก สุขเกษม (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The aims of this study were to compare hardness of enamel, eroded enamel by a Cola drink and remineralized enamel by casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) and to compare remineralization effect of CPP-ACP to that of artificial saliva. Thespecimens were prepared from 10 extracted human premolars, sectioned longitudinally in bucco-lingual direction. The hardness was measured at cutting surface 200 microns away from outer surface. Baseline vickers hardness was measured. The demineralization process was done by immersion of specimens in a Cola drink. The hardness measurements were repeated for demineralization hardness. For remineralization process, the demineralized specimens were randomly divided into 4 groups and 4 regimens of remineralization used CPP-ACP, artificial saliva, CPP-ACP with artificial saliva and deionized water. The hardness measurements were repeated for remineralization hardness. Baseline, demineralization and remineralization hardness were analyzed with Paired-sample T-Test and One Way ANOVA. The results from this in vitro study showed that the Cola drink had significantly negative effect on enamel hardness, while CPP-ACP, artificial saliva and CPP-ACP with artificial saliva had significantly positive effect on enamel hardness after demineralization. The remineralization effect of CPP-ACP and CPP-ACP with artificial saliva was significantly higher than that of artificial saliva.